Project management improvement with proposed project management office: case in palm oil industries and machineries - Hutapea, Benyamin Tangihon; Nasution, Harmein; Hidayati, Juliza (Universitas Mercu Buana, 2024)
Multi-project management are a huge challenge in organizations project management. In order to improve the success of multi-project practice, organizations are begun to considering to implement Project Management Office (PMO) inside their organization structure as a single structure that focused on managing project portfolio inside organization. PMO is a type of business-oriented organizational structure that supports the enterprises business strategy, development and describes the rationale of how a project-portfolio management organization shold be. The major challenge in this qualitative research is to identify which variables that proposed PMO department have to take concern of and formulize a relevant PMO model, scope and project management process to its organization. Literature reviews enrich that the ideal PMO should have able to integrate organizations project portfolio, standardize project management methods, providing tools, managing continuous improvement and designing effective communication system. As results, proposed PMO department will be adopting controlling model, have strategic, tactic and operation scope with their own maturity level based on PMO maturity cube and a new proposed project management process, involving entire stakeholders within project environment.